Analysis of Lead (Pb) Metal Levels of Kepah Clam (Meretrix sp.) and its Correlation to Sediment Pb Levels on the Coastal District of Paiton - Rasyada, Almazahra Aulia; Kuntjoro, Sunu (LenteraBio : Berkala Ilmiah Biologi, 2024)
The coast in Paiton District has potentially contaminated with the heavy metal lead (Pb) due to its location near PLTU areas, fishing ports, tourism and residential areas. Kepah clam (Meretrix sp.) lives along the Paiton coast is susceptible to exposure Pb metal, therefore kepah used as a bioindicator of heavy metal pollution in waters. The aim of this research to analyze Pb levels of kepah and sediments on Paiton coast and also the correlation between kepah’s Pb levels and sediment’s Pb levels. Samples were obtained from three beaches, including Duta, Pondok Kelor, and TPI. Sea-water quality measured using physic-chemical parameters. Analysis Pb levels in kepah clams and sediments was performed using atomic absorption spectrophotometry method. Data was tested using Pearson correlation to determine correlation between kepah Pb and sediment Pb levels. Results showed that kepah Pb levels on the three beaches were 1.4 ± 0.1 ppm; 1.5 ± 0.2 ppm; and 1.5 ± 0.1 ppm, while sediment Pb levels on the three beaches were 2.1 ± 0.1 ppm; 2.3 ± 0.3 ppm; and 2.3 ± 0.1 ppm. Level of Pb in sediment and kepah clams were correlated positively, means the higher Pb content in the sediment, the higher Pb absorbed by the clams too.